Versatile "click chemistry" Approach to functionalizing silicon quantum dots: Applications toward fluorescent cellular imaging - Cheng, X.; Lowe, S.; Ciampi, Simone; Magenau, A.; Gaus, K.; Reece, P.; Gooding, J. (American Chemical Society, 2014)
In this study, we describe a solution procedure for the preparation and surface modification of photostable colloidal silicon quantum dots (SiQDs) for imaging of cancer cells. Photoluminescent SiQDs were synthesized by reduction of halogenated silane precursors using a microemulsion process. It was shown that 1,8-nonadiyne molecules could be grafted onto the surface of hydrogen-terminated SiQDs via ultraviolet (UV)-promoted hydrosilylation, demonstrated by Fourier transform infrared spectroscopy (FTIR) measurements. In addition, various azide molecules were coupled onto nonadiyne-functionalized particles, rendering particles dispersible in selected polar and nonpolar solvents. The photoluminescence of functionalized SiQDs was stable against photobleaching and did not vary appreciably within biologically applicable pH and temperature ranges. To demonstrate compatibility with biological systems, water-soluble SiQDs were used for fluorescent imaging of HeLa cells. In addition, the SiQDs were shown to be non-cytotoxic at concentrations up to 240 µg/mL. The results presented herein provide good evidence for the versatility of functionalized SiQDs for fluorescent bioimaging application.